Analysis of Factors Associated with the Success of Early Breastfeeding Initiation in Pregnant Women at Bhayangkara Hospital - Primasari Oktaviani; Putri Azzahroh; Vivi Silawati (Rajaki of Tulip Medika Publisher, 2024)
Abstract Background: The percentage of early breastfeeding initiation process in Lampung Province in 2016 started to get breast milk less than one hour at 41.5% and within one hour or more at 7.0%. Various factors that cause the low practice of IMD in Indonesia are caused by the level of education, attitude and motivation of breastfeeding mothers, and influenced by the behavior and actions of midwives who do not counsel about IMD during pregnancy and do not support the management of IMD in normal delivery care (APN) and family support. Research Objective: To determine the factors associated with early initiation of breastfeeding among laboring mothers at Bhayangkara Tk I Pusdokkes Polri Hospital. Methodology: The type of research used was quantitative research with cross sectional approach. The population in this study were all mothers who gave birth at Bhayangkara TK I Pusdokkes Polri Hospital a total of 53 respondents with a sample of 47 people using purposive sampling technique. Data was collected using a questionnaire. Data analysis was univariate and bivariate (Chi-square test). Research Results: The results of univariate analysis that the success of IMD was successful at 31 (66.6%), positive motivation at 28 (59.6%), positive maternal attitude at 27 (57.4%), positive husband support at 36 (76.6%), positive officer role at 35 (74.5%). Bivariate results showed the relationship between maternal motivation with a value of (p-value = 000), maternal attitude (p-value = 0.000), husband support (p-value = 0.029), and health worker role (p-value = 0.001). Conclusion: There is a relationship between maternal motivation, maternal attitude, husband's support and the role of health workers with early breastfeeding initiation in newborns at Bhayangkara Tk I Pusdokkes Police Hospital. Suggestion: For health workers to provide as much information as possible about early breastfeeding initiation and motivate laboring mothers to perform early breastfeeding initiation. Keywords: early breastfeeding initiation, motivation, husband's support, role of health worker, mother's attitude. Literature: 20 (2012-2020)